Peripheral ameloblastoma. - Niccoli-Filho, W.; Gomes, M. G.; Raldi, F. V.; Seraidarian, P. I. (Nihon University School of Dentistry, 1997)
A case of peripheral ameloblastoma in a 57-years-old woman is presented, along with a discussion of the clinical and histological characteristics of the lesion. After clinical and radiographic examinations, and with a differential diagnosis of pyogenic granuloma, an excisional biopsy was performed and the material collected was sent for histological examination. On the basis of the histopathological diagnosis, a second operation was performed with a wide safety margin, including bone tissue, which did not show any involvement with the odontogenic neoplasm.
Keywords: ameloblastoma; basement membrane; biopsy; case report; cell nucleus; differential diagnosis; female; follow up; human; mandible; mandible tumor; middle aged; oral surgery; pathology; pyogenic granuloma; radiography; ultrastructure; Alveolectomy; Ameloblastoma; Basement Membrane; Biopsy; Cell Nucleus; Diagnosis, Differential; Female; Follow-Up Studies; Granuloma, Pyogenic; Humans; Mandible; Mandibular Neoplasms; Middle Aged